Doped silica fibre thermoluminescence measurements of radiation dose in the use of 223Ra - Bradley, David A.; Abdul Sani, Siti Fairus; Ahmad Shaharuddin, Siti Shafiqah; Collins, Sean M.; Hugtenburg, Richard P.; Abdul Rashid, Hairul Azhar; Zulkepley, Nurul Najua; Maah, Mohd Jamil (Elsevier B.V., 2018)
Using tailor-made sub-mm dimension doped-silica fibres, thermoluminescent dosimetric studies have been performed for α-emitting sources of 223RaCl2 (the basis of the Bayer Healthcare product Xofigo®). The use of 223RaCl2 in the palliative treatment of bone metastases resulting from late-stage castration-resistant prostate cancer focuses on its favourable uptake in metabolically active bone metastases. Such treatment benefits from the high linear energy transfer (LET) and associated short path length (<100 µm) of the α-particles emitted by 223Ra and its decay progeny. In seeking to provide for in vitro dosimetry of the α-particles originating from the 223Ra decay series, investigation has been made of the TL yield of various forms of Ge-doped SiO2 fibres, including photonic crystal fibre (PCF) collapsed, PCF uncollapsed, flat and single-mode fibres. Irradiations of the fibres were performed at the UK National Physical Laboratory (NPL). Notable features are the considerable sensitivity of the dosimeters and an effective atomic number Zeff approaching that of bone, the glass fibres offering the added advantage of being able to be placed directly into liquid. The outcome of present research is expected to inform development of doped fibre dosimeters of versatile utility, including for applications as detailed herein.